Laser Cutting and Piercing of Thin Films and Flexible Substrates - Kirti; Pawan Kumar; Sandeep Kumar Khatkar; Amit Gupta (Innovative Research Thoughts, 2023)
The processing of thin films and flexible substrates often makes use of lasers for a variety of tasks, including cutting and piercing. The production of delicate patterns, holes, and forms in a number of materials, such as metals, polymers, and ceramics, is made possible via the use of these technologies, which provide accurate and time-efficient processes. Since lasers are capable of cutting and penetrating materials with thicknesses ranging from a few microns to several millimetres, they are well suited for use in microfabrication, electronics, and biomedical engineering applications. The process of laser cutting involves directing a high-powered laser beam onto the material, which then melts or vaporises the region of interest in the material. This procedure is handled by a computer-aided design (CAD) system, which enables accurate placement of the laser beam as well as the shape of it. The usage of laser cutting is especially beneficial when it comes to the production of intricate and detailed forms, as well as the creation of tiny elements with high aspect ratios. In the process of laser piercing, the laser beam is concentrated on a single location in order to make a tiny hole in the material. The material will melt and evaporate as a result of the heat created by the laser, which will result in the creation of a hole with a diameter of only a few microns. Both the drilling of holes in electronic components and the creation of vias in printed circuit boards are common applications for the technique of laser piercing. The fact that laser cutting and piercing are non-contact processes removes the need of coming into direct physical touch with the item being worked on, which in turn lowers the likelihood that the material may be harmed or contaminated. In addition, these procedures are ideal for large-volume production operations because to their high level of accuracy as well as their high rate of speed. However, the thickness of the material being processed, the characteristics of the material being processed, and the cost of the laser equipment may all act as potential limitations for laser cutting and piercing.